Hetyckie rytuały budowlane : wprowadzenie, charakterystyka i obecność w innych kulturach - Jagiełło, Mieszek (Instytut Historyczny Uniwersytetu Wrocławskiego, 2020)
The following paper examines Hittite building rituals in a broad context by summarizing scholarship on the topic, defining different aspects of building rituals, considering their political and religious teleology, as well as searching for possible connections outside the Hittite culture. The text contains summaries of selectedrituals mentioned in Hittite sources. Moreover, the author puts forward a hypothesis, according to which theTheban founding myth about Cadmus might derive from Hittite festivities connected to building rituals.